“Breaking the mould”: Resisting the stereotypes of being a Black Canadian student-athlete - Nartey, Humphrey; James, Carl E. (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
This article examines how stereotypes operate in the social construction of Black Canadian male student-athletes and how those stereotypes frame these students’ lived experiences in relation to race, athletic ability, and academic performance. From qualitative interviews with twenty current and former Black Canadian student-athletes, we found that they largely resisted and challenged the stereotypes of being primarily athletes and less students. In various ways, they sought to demonstrate that they possessed the skills needed to be academically successful students with the ability to balance their athletic and academic responsibilities and commitments. This was evident in their having obtained the required grades to enter university, receiving athletic scholarships, maintaining playing eligibility, graduating from university, and going on to pursue graduate studies.